ITGB1 Drives Hepatocellular Carcinoma Progression by Modulating Cell Cycle Process Through PXN/YWHAZ/AKT Pathways - Xie, Jinghe; Guo, Tingting; Zhong, Zhiyong; Wang, Ning; Liang, Yan; Zeng, Weiping; Liu, Shoupei; Chen, Qicong; Tang, Xianglian; Wu, Haibin; Zhang, Shuai; Ma, Keqiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
Integrin β1 (ITGB1), which acts as an extracellular matrix (ECM) receptor, has gained increasing attention as a therapeutic target for the treatment of hepatocellular carcinoma (HCC). However, the underpinning mechanism of how ITGB1 drives HCC progression remains elusive. In this study, we first found that ITGB1 expression was significantly higher in HCC tissues than in normal controls by bioinformatics analysis. Furthermore, bioinformatics analysis revealed that paxillin (PXN) and 14-3-3 protein zeta (YWHAZ) are the molecules participating in ITGB1-regulated HCC tumor cell cycle progression. Indeed, immunohistochemistry (IHC) revealed that ITGB1, paxillin, and YWHAZ were strongly upregulated in paired HCC tissue compared with adjacent normal tissues. Notably, the inhibition of ITGB1 expression by small interfering RNA (siRNA) resulted in the downregulated expression of PXN and YWHAZ in primary HCC cells, as assessed by western blot and immunostaining. In addition, ITGB1 knockdown markedly impaired the aggressive behavior of HCC tumor cells and delayed cell cycle progression as determined by cell migration assay, drug-resistance analysis, colony formation assay, quantitative real-time polymerase chain reaction (qRT-PCR), and cell cycle analysis as well as cell viability measurements. More importantly, we proved that xenograft ITGB1high tumors grew more rapidly than ITGB1low tumors. Altogether, our study showed that the ITGB1/PXN/YWHAZ/protein kinase B (AKT) axis enhances HCC progression by accelerating the cell cycle process, which offers a promising approach to halt HCC tumor growth.